A critical analysis of prisons as discourse communities: an examination of Whawha prison complex. - Gohodzi, Isheanesu (Midlands State University, 2014)
This research looks at the prison community as a discourse community. The study also provides a sociolinguistic analysis of the language used at Whawha Medium Offenders Prison. Through the analysis of language the study also explores certain aspects of prison life at Whawha prison complex. The study uses the ‘sociolinguistics theory’. The research examines Whawha Prison Complex as a discourse community, investigates how the inmates at Whawha Prison Complex use language in a peculiar way, explores the origins of cant, slang and jargon used at Whawha Prison Complex and also teaches the way prisoners at Whawha Prison Complex communicate